The Holocene history of the North American Monsoon: 'known knowns' and 'known unknowns' in understanding its spatial and temporal complexity - Metcalfe, Sarah E.; Barron, J.A.; Davies, S.J. (Elsevier, 2015)
Evidence for climatic change across the North American Monsoon (NAM) and adjacent areas is reviewed, drawing on continental and marine records and the application of climate models. Patterns of change at 12,000, 9000, 6000 and 4000 cal yr BP are presented to capture the nature of change from the Younger Dryas (YD) and through the mid-Holocene. At the YD, conditions were cooler overall, wetter in the north and drier in the south, while moving into the Holocene wetter conditions became established in the south and then spread north as the NAM strengthened. Until c. 8,000 cal yr BP, the Laurentide Ice Sheet influenced precipitation in the north by pushing the Bermuda High further south. The peak extent of the NAM seems to have occurred around 6000 cal yr BP. 4000 cal yr BP marks the start of important changes across the NAM region, with drying in the north and the establishment of the clear differences between the summer-rain dominated south and central areas and the north, where winter rain is more important. This differentiation between south and north is crucial to understanding many climate responses across the NAM. This increasing variability is coincident with the declining influence of orbital forcing. 4000 cal yr BP also marks the onset of significant anthropogenic activity in many areas. For the last 2000 years, the focus is on higher temporal resolution change, with strong variations across the region. The Medieval Climate Anomaly (MCA) is characterised by centennial scale ‘megadrought’ across the southwest USA, associated with cooler tropical Pacific SSTs and persistent La Niña type conditions. Proxy data from southern Mexico, Central America and the Caribbean reveal generally wetter conditions, whereas records from the highlands of central Mexico and much of the Yucatan are typified by long -term drought. The Little Ice Age (LIA), in the north, was characterised by cooler, wetter winter conditions that have been linked with increased frequency of El Niño’s. Proxy records in the central and southern regions reveal generally dry LIA conditions, consistent with cooler SSTs in the Caribbean and Gulf of Mexico. This synthesis demonstrates that in some periods, one major forcing can dominate across the whole area (e.g. insolation in the early-mid Holocene), but at other times there is strong variability in patterns of change due to the differential impact of forcings such as the Pacific Decadal Oscillation (PDO) and the Atlantic Multidecadal Oscillation (AMO) on precipitation seasonality.